BENTUK MOTIFSULAMAN APLIKASI KENAGARIAAN BARUNG-BARUNG BELANTAI - SONIA SRIDEVI, Drs. Mediagus, M. Pd. (Universitas Negeri Padang, 2019)
This research aimed to describe about figure, placement and technique on product named embroidery application that come from Barun-barung Belantai at Shouth pesisir regerency. The subject of this research were some of entrepreneurs and employees of this business. The data which were the gained in the kind of notes, documentations, recording and the product it self that is made by the entrepreneur of embroidery application. The data that had been collected is processed in qualitative analysis technique. The results of the research were the natural design form of plants, the shape of waves on the asean which is distillation with Daun Kambeh, Bungo Durian, Daun Pepaya, Bungo Gambia, Kaluak Paku and then the geometry form of Rangkiang. The disposition of the design was matchedwith the product form like men and women moslem wears and for women’s moslem prayer dresses also. The technique used in the embroidery application making process is paste technique that make this embroidery becomes one of the unique by South Pesisir Selatan regerency from other embroidery crafts ingeneral.Keyword: Dessign Form, Disposition, Technique